Access to veterinary care: evaluating working definitions, barriers, and implications for animal welfare - Pasteur, Kayla; Diana, Alessia; Yatcilla, Jane Kinkus; Barnard, Shanis; Croney, Candace C. (Frontiers in Veterinary Science, 2024)
Humans have a moral obligation to meet the physical and mental needs of the animals in their care. This requires access to resources such as veterinary care, which is integral to achieving animal welfare. However, ‘access’ to veterinary care is not always homogenous across communities and currently lacks a consistent definition. The objectives of this scoping review were to (1) understand how ‘access’ to veterinary care has been defined in the literature, (2) map a broad list of potential barriers that may influence access to veterinary care, and (3) identify how access to care impacts the welfare of companion and livestock animals. The literature search yielded a total of 1044 publications, 77 of which were relevant to our inclusion criteria, and were published between 2002 and 2022. Studies were most frequently conducted in the United States (n =17) and Canada (n = 11). Publications defining access to veterinary care (n = 10) or discussing its impacts on animal welfare (n = 13) were minimal. However, barriers to accessing veterinary care were thoroughly discussed in the literature (n = 69) and were categorized into ten themes according to common challenges and keywords, with financial limitations (n = 57), geographic location (n = 35), and limited personnel/equipment (n = 32) being the most frequently reported. The results of this scoping review informed our proposed definition of access to veterinary care. Additionally, our findings identified a need to further investigate several understudied barriers relating to access to care (i.e., veterinarian-client relationship, client identity) and to better understand how they potentially affect animal welfare outcomes.